2021
DOI: 10.3390/cancers13194944
|View full text |Cite
|
Sign up to set email alerts
|

SSTR2 in Nasopharyngeal Carcinoma: Relationship with Latent EBV Infection and Potential as a Therapeutic Target

Abstract: Nasopharyngeal carcinoma (NPC) is a malignant epithelial tumor, most commonly located in the pharyngeal recess and endemic to parts of Asia. It is often detected at a late stage which is associated with poor prognosis (5-year survival rate of 63%). Treatment for this malignancy relies predominantly on radiotherapy and/or systemic chemotherapy, which can be associated with significant morbidity and impaired quality of life. In endemic regions NPC is associated with infection by Epstein–Barr virus (EBV) which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…In addition, NF-κB signalling may also be affected by the activation of EBV-miR-BART13, which is a type of EBV miRNA. In vivo and in vitro studies have shown that these miRNAs can promote the growth and metastasis of NPC cells [41,42]. MAPK plays a vital role in the process of cell proliferation, differentiation, transformation, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NF-κB signalling may also be affected by the activation of EBV-miR-BART13, which is a type of EBV miRNA. In vivo and in vitro studies have shown that these miRNAs can promote the growth and metastasis of NPC cells [41,42]. MAPK plays a vital role in the process of cell proliferation, differentiation, transformation, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Emanuel, O. et al [ 19 ] offered a comprehensive and up-to-date summary of NPC, focusing on the role of somatostatin receptor 2 (SSTR2), a key tumour biomarker and promising target for imaging and therapy.…”
Section: Ebv-associated Malignancies and Ebv-targeted Therapiesmentioning
confidence: 99%
“…Persistently elevated EBV antibody levels are considered a major risk factor for NPC. [1][2][3] NPC is a regional cancer, with high incidence rates in southern China and Southeast Asia. 2 4 The disease is classified into two types based on histological analysis: nonkeratinising squamous cell carcinoma and keratinising squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%